Maintaining and Supporting Seniors’ Wellbeing through Foreign Language Learning: Psycholinguistics of Second Language Acquisition in Older Age - Pikhart, Marcel; Klimova, Blanka (International journal of environmental research and public health, 2020)
This study concerns aspects of positive psychology connected to foreign language learning (FLL) in an older healthy generation. The positive psychology perspective stresses the positive aspects of improved wellbeing in participants who engage in various activities, particularly mental and brain-training practices. Therefore, the aim of this study was to explore older people’s subjective feelings connected to their FLL as one of the crucial ways to improve their quality of life (QoL). The objective of the research was to determine the subjective satisfaction level of the participants of a second language (L2) acquisition course. The research sample (experimental group) consisted of 105 respondents who were Czech citizens and 55+ years old. Two control groups were set up. The first (young control) consisted of 102 young adults (university students), also Czech citizens, aged between 19 and 23 years. The second control group (elderly control) consisted of 102 subjects older than 55 years, similar in age to the experimental group. A standardized online questionnaire survey was the principal research method, identical both for the experimental and control groups. The findings clearly showed that language training significantly improved the subjective positive feelings and wellbeing of the older participants, regardless of their objective progress in FLL itself. These results stood in opposition to the young control group and were different from the elderly control group. The results revealed that FLL is an effective tool for enhancing the overall wellbeing of older people, which was shown in their expression of their feelings of happiness, satisfaction, and positive motivation to learn an L2. In addition, FLL objectively affected their mental health in a positive way and expanded their social networks. Moreover, FLL was a meaningful activity for them, despite the weak objective learning outcomes due to the decline of cognitive functions, helping them find their general purpose of life, as well as life motivation as expressed in the survey. These findings are crucial, as it has already been proven that wellbeing is directly connected with good health and longevity. Therefore, national governments and all stakeholders dealing with the present issue of the aging population should pay undivided attention to the enhancement of older people’s wellbeing by all possible intervention approaches, including FLL. There is limited research into the issue and the findings of this investigation could be an impetus for further research into the topic from the perspectives of cognitive science, psychology, and psycholinguistics.